PERANCANGAN APLIKASI INFORMASI WARISAN BUDAYA MEGALITIK Studi Kasus: Pasemah Megalitik Sumatera - Santo Tjhin; Rahmadia Putri (Jurnal Dimensi DKV Seni Rupa dan Desain, 2021)
AbstractDesigning Megalithic Cultural Heritage Information Application (Case Study: Sumatran Megalithic Pasemah). Pasemah plateau is a historic plateau. There is a prehistoric heritage site that has a megalithic tradition because it has megalithic artifacts from the megalithic era. In 2012, Pasemah's megalithic cultural heritage was registered by the Government of Pagaralam as one of the world's heritages. Researchers designed the Pasemah megalithic cultural heritage application, which is an active effort to support the development of the megalithic cultural heritage in Pasemah through appropriate technological innovations. By utilizing internet technology in the form of applications can disseminate information quickly and reach the wider community. The method in designing the application uses the Design Thinking method. The design is more focused on strengthening the concept of the story "The Story of Megalithic Culture in Pasemah". The research applies storytelling data in customized technology as knowledge, intending to stimulate the process of disseminating information and knowledge about megalithic cultural heritage in Pasemah to the wider community. The design of this application is also expected to be a means of educating and educating the people of Pasemah especially with the cultural heritage of the megalithic era in Pasemah.Keywords: cultural heritage, megalithic, Pasemah apps Abstrak Perancangan Aplikasi Informasi Warisan Budaya Megalitik (Studi Kasus: Pasemah Megalitik Sumatera). Dataran Pasemah merupakan dataran tinggi bersejarah. Terdapat sebuah situs peninggalan prasejarah yang memiliki tradisi megalitik, karena memiliki artefak megalit dari jaman megalitik. Pada 2012, warisan megalitik budaya Pasemah didaftarkan oleh Pemerintah Pagaralam sebagai salah satu warisan dunia. Peneliti merancang aplikasi peninggalan megalitik budaya Pasemah, sebagai suatu upaya tindakan dalam mendukung pengembangan warisan budaya megalitik di Pasemah melalui inovasi teknologi tepat guna. Dengan memanfaatkan teknologi internet dalam bentuk aplikasi dapat menyebarkan informasi secara cepat dan menjangkau masyarakat secara luas. Metode dalam mendesain aplikasi menggunakan metode Design Thinking. Desain lebih difokuskan dalam memperkuat konsep cerita “Kisah Budaya Megalitik di Pasemah”. Penelitian menerapkan data storytelling dalam teknologi customized sebagai pengetahuan baru, dengan tujuan dapat menstimulasi proses penyebaran informasi dan pengetahuan akan cagar budaya megalitik di Pasemah kepada masyarakat luas. Perancangan aplikasi ini diharapkan menjadi sarana dalam mendidik dan mencerdaskan khususnya masyarakat Pasemah dengan warisan budaya era megalitik di Pasemah.Kata kunci: cagar budaya, megalitik, aplikasi Pasemah